Changes in Bone Conduction Implant Geometry Improve the Bone Fit in Mastoids of Children and Young Adults. Issue 10 (December 2020) - Wenzel, Claudia; Schilde, Sebastian; Plontke, Stefan K.; Rahne, Torsten
Abstract : Objectives: In 2012 the first active bone conduction implant was introduced, but did not fit into the mastoids of some adults and many children. Thus, a geometry change of the transducer was proposed (BCI 602). In this study, we aimed to determine whether these changes improved the mastoid cavity fit of the implant in children and young adults. Design: We retrospectively analyzed computed tomography scans of 151 mastoids from 81 children and adolescents (age range, 5 mo to 20 yr) and 52 control mastoids from 33 adults. After three-dimensional reconstruction of the temporal bone from computed tomography, we virtually implanted the BCI 602 into the mastoids, and compared the bone fit with that of the BCI 601. Results: The BCI 602 could be virtually implanted in 100% of patients ≥12 years old, while the BCI 601 transducer could be completely embedded in the bone of only 70% of these mastoids. Moreover, virtual implantation of the BCI 602 was possible in 75% of children 3 to 5 years of age, while the BCI 601 did not fit in the mastoids of any patients under 5 years old without the use of lifts. Conclusions: Compared to the BCI 601, placement of the BCI 602 allegedly requires less bone removal. The newer BCI 602 transducer is more likely than its predecessor to be completely accommodated in the mastoid bone among all age groups and indications. Preoperative planning is still recommended to avoid exposure of delicate structures. Abstract : Supplemental Digital Content is available in the text